Pelaksanaan Kurikulum Merdeka di SMP Negeri 1 Banuhampu - Novelia, Na Tasya Ramadani; Zuwirna, Zuwirna; Hidayati, Abna; Yeni J, Fetri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to identify the implementation of the Kurikulum Merdeka and obstacles in the implementation of the Kurikulum Merdeka at SMP Negeri 1 Banuhampu. The study of the implementation of the Kurikulum Merdeka at SMP Negeri 1 Banuhampu can be carried out using a qualitative approach with a descriptive research method. The data collection technique uses observation, interview, and documentary research techniques to collect data from participants (including principals, curriculum representatives and teachers) involved in the implementation of the self-directed learning program at SMP Negeri 1 Remaja. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study show that the Kurikulum Merdeka has been implemented as expected. However, in its implementation, teachers need guidance, including attending training sessions at schools to learn more about the Kurikulum Merdeka and continuing to activate the learning community to identify shortcomings and things that need to be improved. In learning, the teachers have carried out the learning process according to the Kurikulum Merdeka and prepared learning tools starting from Learning Outcomes (CP), Learning Objectives Flow (ATP), Learning Objectives (TP), and teaching modules. Obstacles in the implementation of the Kurikulum Merdeka are human resources who do not understand the implementation of the Kurikulum Merdeka and inadequate facilities and infrastructure at SMP Negri 1 Banuhampu so that it slows down the learning process in the classroom.